2022
DOI: 10.1186/s13020-022-00677-6
|View full text |Cite
|
Sign up to set email alerts
|

Chinese integrated guideline on the management of gastric precancerous conditions and lesions

Abstract: The standardized diagnosis and management of gastric precancerous conditions and lesions are important to prevent gastric cancer. This guideline, created by 5 traditional Chinese medicine and Western medicine associations, based on the current morbidity and diagnosis and treatment of gastric precancerous conditions and lesions, provides specific key points and strategies for diagnosis and treatment in the following five aspects: definition and epidemiology, diagnosis and stage, surveillance, treatment and effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 161 publications
0
5
0
Order By: Relevance
“…The AITonguequiry model has demonstrated an enhanced ability to detect PLGC before endoscopy. In a cross-sectional survey conducted by the Digestive Endoscopy Society of the Chinese Medical Association in 2014, involving 8892 patients diagnosed with chronic gastritis via gastroscopy across 10 cities and 33 centers, it was found that 56.7% of patients had PLGC [ 36 , 37 ]. Notably, among patients recommended for endoscopic examination according to the AITonguequiry model, the detection rate of PLGC reached 73%.…”
Section: Discussionmentioning
confidence: 99%
“…The AITonguequiry model has demonstrated an enhanced ability to detect PLGC before endoscopy. In a cross-sectional survey conducted by the Digestive Endoscopy Society of the Chinese Medical Association in 2014, involving 8892 patients diagnosed with chronic gastritis via gastroscopy across 10 cities and 33 centers, it was found that 56.7% of patients had PLGC [ 36 , 37 ]. Notably, among patients recommended for endoscopic examination according to the AITonguequiry model, the detection rate of PLGC reached 73%.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic risk factors were not included in this study. GC shows familial aggregation in ~10% of cases, and there is an inherited genetic predisposition with known specific gene mutations in up to 3% of cases [ 47 ]. The role of low-penetrance genes in GC is an important step in genetic counselling since an early therapeutic endoscopic intervention could be offered.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese medicine and its active components have demonstrated distinct advantages in influencing the release of inflammatory factors and treating GPL ( 120 ). However, the underlying mechanisms how they affect the inflammatory microenvironment to prevent GPL, along with their true effect in GPL clinical trials, remain unclear.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%